Beauty Training and Financial Management Empowerment for KWT Sewagati Members : Pemberdayaan Pelatihan Kecantikan Dan Manajemen Keuangan Bagi Anggota KWT Sewagati - Rochmad Bayu Utomo; Andiani Pratiwi, I Gusti Ayu Agung Mas; Septhia Fadhilla Nurkhasanah; Putri Maharani, Desak Putu (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Empowering housewives is a crucial strategy for supporting the household economy in Indonesia post-Covid-19. The pandemic has led to decreased income due to job losses and reduced economic activity. By improving skills, access to capital, and business opportunities, housewives can increase family income sources. Programs such as entrepreneurship training, access to digital marketplaces, and micro-capitalization help build independent businesses. This increases family economic resilience and national recovery through MSMEs. In the Pasekan Lor hamlet, the majority of housewives act as household managers with free time but lack skills. This situation opens up opportunities for empowerment and financial independence for housewives. The Community Service Program (PKM) activity for housewives in the Pasekan Lor RT 04 Pasekan Lor neighborhood, Balecatur, Gamping, Yogyakarta, aims to change the mindset of housewives towards entrepreneurship, specifically in the beauty sector, particularly makeup, to improve welfare. The economic empowerment